2013
DOI: 10.1097/mol.0b013e32835da13c
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic gene targeting approaches for the treatment of dyslipidemias and atherosclerosis

Abstract: New therapies for lowering lipid levels are now being tested in clinical trials, and both antisense oligonucleotide and RNAi-based therapies have shown promising results in lowering cholesterol levels. However, the modulation of inflammatory component in atherosclerosis by gene therapy and targeting of the effects to plaques are still difficult challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 70 publications
0
13
0
Order By: Relevance
“…Novel gene therapy approaches for the treatment of hyperlipidemia have been directed. New therapies for lowering lipid levels are now being tested in clinical trials, and both RNAi-based and antisense oligonucleotide therapies have revealed promising results in lower in cholesterol levels (Mäkinen & Ylä-Herttuala, 2013).…”
Section: Therapeutic Gene Targetingmentioning
confidence: 99%
“…Novel gene therapy approaches for the treatment of hyperlipidemia have been directed. New therapies for lowering lipid levels are now being tested in clinical trials, and both RNAi-based and antisense oligonucleotide therapies have revealed promising results in lower in cholesterol levels (Mäkinen & Ylä-Herttuala, 2013).…”
Section: Therapeutic Gene Targetingmentioning
confidence: 99%
“…Antisense and RNA interference (RNAi) technology are most commonly used strategies to eliminate or silence the expression of target genes [66]. These technologies are also used as a tool to study gene function in cancer cells [67].…”
Section: Gene Targetingmentioning
confidence: 99%
“…According to unpublished reports, the drug decreased apoC-III levels up to 78% in a Phase I study of 32 subjects and is currently undergoing a Phase II trial [203,204]. Similar gene silencing approaches have been carried out through the use of antisense oligonucleotides and RNAi directed against apoB-100 and PCSK9, as have been reviewed elsewhere [132]. …”
Section: Apoc-iiimentioning
confidence: 99%